Trust, child care technology choice and female labor force participation - Mayssun el Attar (Institute for the Study of Labor (IZA), 2007)
In this paper we test the effect of trust on the choice of child care technology. We estimate individual-level trust as a latent attribute using survey questions on personal attitudes by applying the econometric methodology by Spady (2007). Compared to other measures of trust, using this technique has several advantages: It makes more efficient use of information by allowing the aggregation of information from several questions and by exploiting additional information from personal and demographic characteristics. It requires very few parametric assumptions and it is conceptually cleaner and more consistent with theory than the proxies or demographic characteristics often used in previous work. Having estimated the individual attitudes to trust using data from the European Social Survey, we analyze their personal, demographic, and regional determinants. We find that trust matters for the degree of externalness of the child care technology people choose. It can therefore be a possible explanation for differences in female labor force participation across countries and across sociological groups.
Keywords: 330; Trust; child care; labor force participation; latent attitudes; item response models; Kinderbetreuung; Vertrauen; Frauenerwerbstätigkeit; Arbeitsangebot; EU-Staaten